Successful limb salvage despite inadequate escharotomy of full-thickness circumferential burns over limbs in a rural hospital aided by telemedicine - Heng, Sophia Si Ling; Lo, Zhen Zhen; Thevarasan Ganandran (Elsevier Inc, 2023)
Deep to full-thickness circumferential burn eschars form an unyielding ‘tourniquet’ constricting the limb, compromising blood supply, and leading to critical limb ischemia. Escharotomies are emergency limb-saving procedures performed to relieve the rising intra-compartmental pressure and restore the blood supply to the peripheries.1 Special training is required, and ideally, experienced emergency physicians, plastic and reconstructive or burn surgeons or other physicians trained in advanced trauma life support should perform escharotomies.2 Complications of escharotomies include bleeding, nerve, or vessel injuries due to inaccurate placement of the incision and inadequate depth of the incision.2 However, in healthcare settings where rural hospitals may be served by young and inexperienced medical personnel, it is difficult to mandate that only certified personnel can perform escharotomies. In our setting, there is only one burn unit in the state that serves a large population and covers part of the neighboring states. Land travel is slow and time-consuming, causing delays in management. Emergency evacuation to the burn unit by flight is difficult to secure due to weather unpredictability and can be costly, especially for patients without health insurance coverage. Without the timely intervention of an escharotomy, it can result in rhabdomyolysis and a host of complications including kidney failure, loss of limb and even death. With telemedicine, escharotomies can be performed in a rural hospital. Experienced healthcare professionals help instill confidence by virtually guiding the team in performing the procedure.3 The benefits of attempting an escharotomy outweigh the risks, especially in a setting where immediate transport to a center with trained experts is not possible. An inadequate escharotomy is the lesser of two evils compared to a delay in performing the procedure. Escharotomies should be attempted in the limb or life-saving situations, with the support of plastic and reconstructive or burn surgeons via telemedicine.